Effects of exogenous corticosterone on in vivo fertilizing capacity of epididymal sperm and reversal of its adverse impactbytocotrffinol in the rat / Noor Azean Anis Abd Aziz - Abd Aziz, Noor Azean Anis (2015)
Elevated corticosterone (CORT) levels are a major indicator of stress. CORT in excess impairs steroidogenesis, and induces both lipid peroxidation and Leydig cell apoptosis. Increased reactive oxygen species levels cause oxidative stress and impair reproductive functions. Tocotrienol is a major chain-breaking antioxidant and has been shown to inhibit lipid peroxidation and reduce oxidative damage. The objectives of this study were to assess the effects of exogenous COR T on the fertilizing capacity of epididymal sperm and to elucidate the beneficial effects oftocotrienol-rich fraction (TRF) supplementation in CORT -treated rats. Epididymides of fertile male rats were surgically-separated at the testis-caput junction. Twenty-four hours post-surgery, animals were given either 5 mg/kg BW corticosterone (CORT5), 10 mg/kg BW corticosterone (CORTlO), 25 mg/kg BW corticosterone (CORT25) or com oil (control) subcutaneously. For the second part of the study, the males were given erther 25 mg/kg BW corticosterone (CORT25) subcutaneously, 100 mg/kg BW tocotrienolrich fraction (TRFl 00) orally, both corticosterone and tocotrienol-rich fraction (CORT25+TRF100), or com oil (control) once daily for 7 consecutive days. Experimental and control rats were co-habitated with proestrus females on day 8 postsurgery. The presence of a sperm-positive vaginal smear on the morning after (day 1 post-coitus) was considered as positive proof of mating and designated as day 1 of pregnancy and experimental males were then sacrificed. Laparotomy was performed on day 8 post-coitus to determine the number of blastocyst implantation. Pregnant animals were left until term. During parturition, the number of viable pups was identified and compared with the number of blastocyst implantation of the same animal to determine fetal loss. Results showed that females mated with COR T -treated rats had lower number of blastocyst implantation and live fetuses, and fetal weight, and increased fetal loss compared to that of control. The reproductive organ weight (testis, epididymis, vas deferens and seminal vesicles) of the males were also reduced. Plasma malondialdehyde level was increased, while plasma ACTH, testosterone, glutathione peroxidase and superoxide dismutase in the COR T25 group were decreased compared to that of control, suggesting a state of CORT -induced oxidative stress. Administration of TRF to COR T -treated rats reversed the effects of COR T on the parameters studied, and returned the parameters towards that of controls. In conclusion, exogenous COR T (25 mg/kg/day) given for 7 consecutive days attenuated the fertilizing capacity of rat epididymal sperm through oxidative stress induction. However, 100 mg/kg/day TRF supplementation reversed the oxidative stress-induced effects of exogenous CORT on the parameters studied and seem to have restored the fertilizing capacity of rat epididymal sperm. As a potent antioxidant, TRF supplementation is able to prevent oxidative stress-induced damage on male reproductive parameters and exerts beneficial effects on male fertility, which is a major clinical concern nowadays.